Examination of Jamaican building societies : issues of efficiency and profitability - Bailey, Karlene ([CCMS] [St. Augustine]TT, 2001)
Explains the developments in the balance sheet and financial ratios of building societies for the 1990s. Focuses on the evolution of the interest margin and interest spread of the building societies.